Transcriptomic profile investigations highlight a putative role for NUDT16 in sepsis. Issue 5 (17th February 2022) - Huang, Susie Shih Yin; Rinchai, Darawan; Toufiq, Mohammed; Kabeer, Basirudeen Syed Ahamed; Roelands, Jessica; Hendrickx, Wouter; Boughorbel, Sabri; Bedognetti, Davide; Van Panhuys, Nicholas; Chaussabel, Damien; Garand, Mathieu
Abstract: Sepsis is an aberrant systemic inflammatory response mediated by the acute activation of the innate immune system. Neutrophils are important contributors to the innate immune response that controls the infection, but harbour the risk of collateral tissue damage such as thrombosis and organ dysfunction. A better understanding of the modulations of cellular processes in neutrophils and other blood cells during sepsis is needed and can be initiated via transcriptomic profile investigations. To that point, the growing repertoire of publicly accessible transcriptomic datasets serves as a valuable resource for discovering and/or assessing the robustness of biomarkers. We employed systematic literature mining, reductionist approach to gene expression profile and empirical in vitro work to highlight the role of a Nudix hydrolase family member, NUDT16, in sepsis. The relevance and implication of the expression of NUDT16 under septic conditions and the putative functional roles of this enzyme are discussed.